Medication compliance of children with epilepsy: a cross-sectional survey - Shanshan Wang; Xu Zhang; Yongqian Wang; Jinfang Zhou (BMC, 2023)
Abstract Background Good medication compliance is very important for the prognosis of children with epilepsy. We aimed to evaluate the status and influencing factors of medication compliance in children with epilepsy and to provide insights to the clinical nursing care of children with epilepsy. Methods We selected epileptic children admitted to Children's Hospital of Nanjing Medical University from February 1, 2022 to August 31, 2022. Self-designed questionnaire and medication compliance scale were used to evaluate the characteristics and medication compliance of children with epilepsy. Pearson correlation analysis and multivariate logistic regression were used to analyze the influencing factors of medication compliance. Results A total of 156 children with epilepsy were included, the incidence of poor compliance in children with epilepsy was 37.18%. Pearson correlation analysis indicated that age(r = 0.622), courses of epilepsy(r = 0.553), parental education level(r = 0.506), monthly household income(r = 0.652) and number of drugs taken(r = 0.577) were correlated with the compliance(all P<0.05). Logistic regression analyses indicated that age ≤ 6 y(OR = 2.104, 95%CI: 1.712 ~ 2.527), courses of epilepsy ≤ 3 years(OR = 2.661, 95%CI: 2.089 ~ 2.941), low parental education level(OR = 1.977, 95%CI: 1.314 ~ 2.351), monthly household income ≤ 5000 RMB(OR = 2.812, 95%CI: 2.194 ~ 3.181), number of drugs taken ≥ 3(OR = 3.025, 95%CI: 2.336 ~ 3.475) were the influencing factors of medication compliance in children with epilepsy(all P<0.05). Conclusions The medication compliance of children with epilepsy needs to be improved, and the medication compliance of children is affected by age, courses of epilepsy, parental education level, monthly household income and number of drugs taken. Clinical medical personnel take targeted nursing measures against these factors to improve the medication compliance of children with epilepsy.